Slope Stability Analysis under Complex Stress State with Saturated and Unsaturated Seepage Flow - Zongyuan Ma; Caihui Zhu; Xiaoliang Yao; Faning Dang (Geofluids)
Seepage flow is one of the primary factors that trigger slopes and landslides’ failure. In this study, the slope stability under saturated or unsaturated conditions is analyzed. The influence of a complex stress state on the slope stability with the saturated or unsaturated seepage flow is proposed in this paper. Firstly, an elastoplastic constituted model for the soil under a complex stress state is established and as a user subroutine of the finite element method code of FLAC. Secondly, the 2D and 3D problems of slope stability influenced by the saturated or unsaturated seepage flow are analyzed via the finite difference method with the influence of the complex stress state. Finally, the influence of the intermediate principal stress and the saturated or unsaturated seepage flow on the slope stability is analyzed in this study.